(untitled) (KIUT Publication, 2025)
According to the World Health Organization (WHO), more than 700,000 people die each year due to infections caused by antibiotic-resistant bacteria. By 2050, this number is projected to reach 10 million. This poses a major threat to the global community, not only from a medical perspective but also from a socio-economic standpoint. Antibiotic resistance negatively affects the reliability of healthcare systems, the duration of disease treatment, and healthcare-related costs.